ADAPTING TO AND DELIVERING REMOTE INSTRUCTION: INTERVIEW WITH PROF. SUSAN GAER - Floris, Flora Debora (TEFLIN Journal, 2020)
Susan Gaer is a Professor Emeritus of Santa Ana College, California. She has an MA in English with emphasis on Teaching English as a Second Language and an MA in Educational Technology from Pepperdine University. She is the President-Elect CATESOL 2018-2020. She is also a Google Certified Innovator, Kahoot Ambassador, Thinglink Educator and Quizlet Teacher Educator. Prof. Gaer has developed a web page https://www.susangaer.com/ that helps teachers to engage students with technology. In this interview, Prof. Gaer shared her viewpoints and some examples on remote instruction.